Методичний інструментарій оцінювання рівня задоволення економічних інтересів стейкхолдерів підприємств кондитерської промисловості - Краснокутська, Наталія Станіславівна; Госн, Салім Клімент (Харківський державний університет харчування та торгівлі, 2019)
Систематизовано показники внесків і стимулів для задоволення економічних інтересів ключових стейкхолдерів підприємств кондитерської промисловості. Обґрунтовано систему показників кількісної оцінки задоволення економічних інтересів ключових стейкхолдерів цих підприємств. Запропоновано структурно-логічну послідовність оцінювання задоволеності економічних інтересів ключових стейкхолдерів підприємства кондитерської промисловості.

Because of the diversity of stakeholders, their interests and the potential benefits of interaction with the company, identification of key stakeholders and the search for effective mechanisms of interaction are possible only within certain industry boundaries. It is the sectoral barriers that significantly affect the level of competition in the industry, the competitive forces of suppliers and buyers, the ability of public organizations to defend the interests of the community, and so on. Confectionery industry is one of the priority sectors for the development of the world market potential, where achieving the harmonization of interests of key stakeholders would contribute to the growth of the potential of this industry. An overview of conducted studies suggests that the authors pay little attention to the sectoral aspect of satisfying the interests of stakeholders, which can vary significantly even by type of industrial production. The aim of the study is to develop methodological tools for assessing the level of satisfaction of the economic interests of stakeholders in confectionery industry enterprises. In order to achieve this goal, the indicators of contributions and incentives for meeting the economic interests of key stakeholders in confectionery industry were systematized; on this basis the system of indicators of quantitative estimation of satisfaction of economic interests of key stakeholders of the confectionery industry is substantiated; The structural-logical sequence of estimation of satisfaction of economic interests of stakeholders of the confectionery industry is presented. Estimation of satisfaction of economic interests of stakeholders is an important element in the system of management of interaction with stakeholders of the enterprise. Achieving harmonization of economic interests between stakeholders and the enterprise will promote their productive co-operation. The proposed tool for evaluating the satisfaction of the economic interests of the stakeholders of the confectionery industry will provide management personnel with the necessary analytical information to improve their interaction with them.
Methodical tools of estimation of the economic interests satisfaction level of the confectionery industry stakeholders
Keywords: оцінка; доходи; витрати; додана вартість; внески; стимули; estimation; economic interest; stakeholder; enterprise; confectionery industry